Post hepatectomy liver failure – A comprehensive review of current concepts and controversies. (October 2018) - Ray, S.; Mehta, N.N.; Golhar, A.; Nundy, S.
Abstract: Post hepatectomy liver failure (PHLF) comprises of a conundrum of symptoms and signs following major hepatic resections. The pathophysiology essentially revolves around disruption of the normal hepatocyte regeneration and disturbed liver homeostasis. Prompt identification of the pre-operative predictors of PHLF in the form of biochemical parameters and imaging features are of paramount importance for any hepatic surgeon and forms the cornerstone of its management. Treatment revolves around a goal-directed resuscitation of the systemic organ failure. Auxiliary support systems such as liver dialysis devices and stem cell therapy are still under investigational trials for treatment of the same. Orthotopic liver transplantation (OLT) is the last resort in most cases not responding to other measures. Highlights: Understanding the mechanics and pathophysiology of post hepatectomy liver failure and its implications in management. Preventive strategies essential for all liver surgeons. Overview of assessing clinical severity and management algorithm of PHLF.